Optimalisasi Artificial Intelligence bagi Guru dalam Pengembangan Instrumen Pembelajaran Berbasis Deep Learning: Integrasi Nilai Etika dalam Pemanfaatan AI di Pendidikan - Herdini; Lenny Anwar S; Susilawati; Abdullah; Dedi Futra; Miftahul Fikriyah (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Artificial Intelligence (AI) use in education is growing, especially in creating Deep Learning-based learning instruments. However, using AI is often not accompanied by an adequate understanding of educational ethics, especially among secondary school teachers. This community service activity aims to improve teachers' ability to integrate educational ethics values in using AI to develop learning instruments. The activity was conducted at SMA Negeri 2 Tapung Hilir, Kampar Regency, involving 34 teachers from various fields of study. The implementation method was a practice-based workshop with a collaborative approach between lecturers and teachers. Data were collected through AI literacy pre-tests and post-tests, observations, and analysis of learning products. The activity results showed an increase in AI literacy of ±20% from an initial score of 3.5 to 4.2. More than 80% of participants could produce AI-based learning instruments that met the criteria of academic validity and educational ethics. These results emphasise the importance of an ethical approach in applying AI technology to ensure the sustainability and humanisation of the educational process.